2017
DOI: 10.1039/c7ra01372h
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the performance of MoS2 based materials for corrosion protection of mild steel in an aggressive chloride environment

Abstract: The incorporation of Fe, Co, and Ni ions resulted in an appreciable increase in the corrosion resistance properties of MoS2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In the thin layer electrolyte, as well as on the metal surface, a non-uniform distribution will occur in the potential, current, and resistance to mass transfer. [7] Different thicknesses of the thin layer electrolyte on the metal surface result in different corrosion rates. Figure 2 qualitatively indicates the relationship between the atmospheric corrosion rate and the thickness of the thin layer electrolyte on the metal surface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the thin layer electrolyte, as well as on the metal surface, a non-uniform distribution will occur in the potential, current, and resistance to mass transfer. [7] Different thicknesses of the thin layer electrolyte on the metal surface result in different corrosion rates. Figure 2 qualitatively indicates the relationship between the atmospheric corrosion rate and the thickness of the thin layer electrolyte on the metal surface.…”
Section: Methodsmentioning
confidence: 99%
“…Under the thin layer electrolyte condition, the traditional electrochemical test method cannot accurately measure the micro‐electrolytic system. In the thin layer electrolyte, as well as on the metal surface, a non‐uniform distribution will occur in the potential, current, and resistance to mass transfer . Different thicknesses of the thin layer electrolyte on the metal surface result in different corrosion rates.…”
Section: Electrochemical Performance Measurement Under a Thin Layer Ementioning
confidence: 99%
“…Good corrosion protection and durability was seen with the MoS 2 -containing sunflower coating, and this was attributed to the formation of a highly ordered barrier coating. Likewise, ArunKumar et al [155] dispersed MoS 2 and doped MoS 2 in sunflower oil, and found that doping MoS 2 with Fe, Co, and Ni ions resulted in an increase in the corrosion-protective properties of MoS 2 . For example, the corrosion current of mild steel was measured as 83 × 10 −6 A cm −2 in a chloride-containing solution.…”
Section: Transition Metal Dichalcogenidesmentioning
confidence: 99%
“…The most studied TMDCs in organic anticorrosion coatings are molybdenum disulfide (MoS 2 ) nanosheets. Because MoS 2 has good chemical and thermal stability, this contributes to the corrosion resistance of the coating. However, layered MoS 2 nanomaterial has a tendency of severe agglomeration in polymer composites. Therefore, the surface organic functionalization of MoS 2 (including noncovalent and covalent modification) is usually used to improve its dispersibility , (Figure ).…”
Section: Fabrication Of 2d Materials Anticorrosive Polymeric Coatingsmentioning
confidence: 99%